814. VARRONIA RUPICOLA. (June 2015) - Hamilton, Martin; Clubbe, Colin; Corcoran, Marcella; Sanchez, Michele
Summary Varronia rupicola (Urb.) Britton (Boraginaceae) a Critically Endangered shrub, restricted to three Caribbean islands – Puerto Rico, Vieques and Anegada—is described and illustrated. Its conservation status and distribution are reviewed.